An unfi nished process: the Western Sahara as a post-scriptum of the colonial period - Novais, Rui (Africana Studia, 2020)
In the North of Africa, between Mauritania and Morocco, lies one of the remaining non-self-governing territories whose decolonization process lingers unfi nished and unresolved: the Western Sahara. After thirty years of illegal Moroccan occupation and sixteen of ceasefi re, one deliberation by the International Court of Justice, several resolutions and various UN-sponsored peace plans, the exile of the Saharwi people persists as well as the denial of its self-determination in clear violation of international law. The result is a ‘state-in-waiting’ considering the possibility of the return to the armed struggle in light of the continued deadlock. This paper offers a brief background of the history of the Saharwi confl ict that will bring into light the factors which account for the maintenance and persistence of the dispute as well as the considerable inherent limitations and extrinsic obstacles facing the last African colony. It will argue that Western Sahara present status - one of only a few nations in the world that remain dominated by a foreign state - is a post-scriptum of the colonial period. The half-hearted support of key external actors which tend to side with each party to the confl ict, along with the uneasiness to move from the ‘culture of non-intervention’ to the ‘culture of non-indifference’ have prevented both a waiting-state to take offi ce and a defi nitive solution for the Western Sahara. Kewords: self-determination, independence, post-colonialism, Western Sahara.